1980
DOI: 10.1113/jphysiol.1980.sp013481
|View full text |Cite
|
Sign up to set email alerts
|

Release of oxytocin induced by salt loading and its influence on renal excretion in the male rat.

Abstract: SUMMARY1. The present study investigates the nature and magnitude of the renal response to plasma levels of oxytocin which might be induced by salt loading.2. Increased plasma osmolality induced by loading with NaCl is an effective stimulus for oxytocin release in the unanaesthetized male rat. Plasma oxytocin concentration was positively correlated (r = 0.77) with plasma osmolality. Plasma oxytocin (,uu./ml.) = 0 37 x (plasma osmolality (m-osmole/kg) -297).3. In anaesthetized Long Evans rats intra-atrial admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
93
3

Year Published

1991
1991
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(108 citation statements)
references
References 25 publications
12
93
3
Order By: Relevance
“…The different potencies of these hormones can be attributed to a relative affinity of OT for its own receptor or its lower affinity for V2 and V1 AVP receptors. On the other hand, studies have suggested a synergistic Neurohypophyseal hormones, ANP and nitrergic system effect of AVP and OT actions on the inner medullary collecting duct where both peptides induce an increase in cAMP accumulation and natriuresis (24,29). OT binds to the V2 AVP receptor because of its structural similarity to AVP.…”
Section: Neurohypophyseal Hormones and The Control Of Sodium And Watementioning
confidence: 99%
See 1 more Smart Citation
“…The different potencies of these hormones can be attributed to a relative affinity of OT for its own receptor or its lower affinity for V2 and V1 AVP receptors. On the other hand, studies have suggested a synergistic Neurohypophyseal hormones, ANP and nitrergic system effect of AVP and OT actions on the inner medullary collecting duct where both peptides induce an increase in cAMP accumulation and natriuresis (24,29). OT binds to the V2 AVP receptor because of its structural similarity to AVP.…”
Section: Neurohypophyseal Hormones and The Control Of Sodium And Watementioning
confidence: 99%
“…It has long been recognized that OT increases renal electrolyte excretion in various species, and that the natriuretic and kaliuretic effects are AVP independent. OT and AVP are secreted simultaneously in response to hyperosmolality and hypovolemia (19,24,25) and when systemically administered (iv or ip) induce natriuresis (26,27). OT is a more potent natriuretic hormone than AVP.…”
Section: Neurohypophyseal Hormones and The Control Of Sodium And Watementioning
confidence: 99%
“…Salt loading an animal will lead to significant increases in tissue Ot mRNA levels and plasma OT concentrations (Balment et al 1980, Van Tol et al 1987, Dellmann et al 1988, Verbalis & Dohinics 1991, Ozaki et al 2004. The effects of altered central AM levels on hypertonic saline-stimulated plasma OT levels were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Both the PVN and SON contain neurons that produce arginine vasopressin (AVP) and/or oxytocin (OT) and project not only to the posterior pituitary gland, but also elsewhere within the central nervous system (CNS). While AVP is well known to control fluid balance by its antidiuretic action, OT, particularly when acting as a neurotransmitter, has been implicated as an important regulator of sodium balance (Balment et al 1980, Van Tol et al 1987, Blackburn et al 1992a,b, 1993, Verbalis et al 1995, Amico et al 2001, Fitts et al 2003, Rigatto et al 2003. We have previously demonstrated that brain-derived AM is a physiologic regulator of AVP secretion (Taylor et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation